Forgetting souls: Lyotard, Adorno, and the Trope of the Jew - Chalfant, Eric (Critical research on religion, 2018)
In this article, I engage in a criticism of Jean François Lyotard's tropological approach to Judaism, arguing that his articulation of the "the jew" as figural projection serves to establish and rigidify a number of freighted binaries such as those between reason and myth, philosophy and theology, and modern and postmodern. In comparison, I posit Theodor Adorno's approach to tropes of Judaism as one which encompasses Lyotard's productive emphases on the role of forgetting in subject formation while loosening these same binaries.